Not all who wander are lost: an argument for searching to browse as a separate information behaviour - McKay, Dana; Twidale, Michael; Buchanan, George (Information Research an international electronic journal, 2025)
Introduction. The relationship between search and browse has long been framed as separate, interleaved and sometimes equal activities. With the shift to nearly exclusive online behaviour, this relationship is changing Method. In light of some surprising incidental research findings, we conduct a critical literature synthesis of literature on search typologies, exploratory search and browsing, especially digital browsing. Analysis. Based on the results of previous work, we identify a gap in previous models of search, specifically searching to browse. Results. The notion of searching to browse changes the relationship between searching and browsing, particularly in a digital context. This new form of both searching and browsing creates a need for new interfaces, particularly for collecting items of interest. Conclusions. We argue for searching to browse as a new form of information behaviour, one that is slowly being accommodated by digital information systems. We recommend that more digital information systems take searching to browse into account.